Alopecia areata and health‐related quality of life: a systematic review and meta‐analysis. (2nd July 2016) - Rencz, F.; Gulácsi, L.; Péntek, M.; Wikonkál, N.; Baji, P.; Brodszky, V.
Summary: Background: No systematic review has yet evaluated the available evidence on health‐related quality of life (HRQOL) in alopecia areata (AA). Objectives: To conduct a systematic review and meta‐analysis of HRQOL studies among patients diagnosed with AA. Methods: A systematic search was performed for papers published between 1946 and 15 December 2014 in Medline, Embase, Web of Science, CINAHL, PsycINFO and the Cochrane Library. Random‐effects meta‐analyses were conducted to pool data. Results: Twenty‐one studies were included, representing a total of 2530 adult patients with AA. Of the 14 different HRQOL measures used in the studies, Dermatology Life Quality Index (DLQI; n  =   8) and SF‐36 ( n  =   7) were the most common. Three AA‐specific HRQOL instruments were identified: Alopecia Areata Quality of Life Index, Alopecia Areata Quality of Life and Alopecia Areata Symptom Impact Scale. The mean pooled DLQI score of patients with AA was 6·3 (95% confidence interval 5·6–7·1). Comparing age‐ and sex‐matched controls, the meta‐analysis of SF‐36 studies revealed significantly reduced HRQOL across the role‐emotional, mental health and vitality domains ( P  <   0·001). Wearing a wig had a positive impact, while scalp involvement, anxiety and depression had a negative impact on HRQOL. Conflicting results were found regarding the association between HRQOL and age, sex, marital status and disease duration. Conclusions: Patients with AA experience significant impairment in HRQOL, especially in the area of mental health. Several generic and dermatology‐specific HRQOL instruments have been used, but no validation studies have confirmed their applicability in AA. The newly developed AA‐specific measures seem very promising; however, a more extensive assessment of validity and reliability is needed. Abstract : What's already known about this topic? A number of studies using various measures have shown that alopecia areata reduces health‐related quality of life. No generic or dermatology‐specific quality‐of‐life instrument has yet been validated in alopecia areata. What does this study add? Comparing patients with AA with the general population, the most significantly impaired domains of health status are role‐emotional, mental health and vitality. Wearing a wig has a positive impact, while scalp involvement, anxiety and depression have a negative impact on quality of life. Linked Comment: Sinclair. Br J Dermatol 2016;175 :461‐462 . Plain language summary available online